2000
DOI: 10.3189/172756400781820877
|View full text |Cite
|
Sign up to set email alerts
|

Influence of geometrical boundary conditions on the estimation of rheological parameters

Abstract: Improved knowledge of geometrical boundary conditions, such as bedrock geometry and surface topography, can contribute significantly to glaciological studies including ice-sheet-flow modelling. Precise thickness and altimetric data allow an estimation of ice-flow direction, the balance velocity and the basal shear stress. These parameters are calculated along a 1160 km profile in East Antarctica using a relationship between shear stress, basal temperature, the Glen flow exponent and a parameter related to stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…By taking into account the ice temperature, one can show that rheological parameters depend on the velocity range so that the ice is a fluid with a non linear viscosity [89]. Finally, Testut et al [90] showed that too many parameters were affecting the flow (sliding, anisotropy, longitudinal stress), so that further studies, based on topography alone, would be unsuccessful for retrieving ice sheet rheological parameters. Recent studies now use the topography to constrain model and, for instance, to improve ice core dating [91,92].…”
Section: Balance Velocity and Ice Dynamicsmentioning
confidence: 99%
“…By taking into account the ice temperature, one can show that rheological parameters depend on the velocity range so that the ice is a fluid with a non linear viscosity [89]. Finally, Testut et al [90] showed that too many parameters were affecting the flow (sliding, anisotropy, longitudinal stress), so that further studies, based on topography alone, would be unsuccessful for retrieving ice sheet rheological parameters. Recent studies now use the topography to constrain model and, for instance, to improve ice core dating [91,92].…”
Section: Balance Velocity and Ice Dynamicsmentioning
confidence: 99%
“…These connections between lakes should be taken into account when modelling flow in this sector. Indeed, Testut and others (2000) observed a major anomaly in the ice flow just above the Adventure Subglacial Trench, between Dome C and Terra Nova Bay, where Siegert and Ridley (1998b) suspected the presence of a hydrological system. The estimated basal temperature was at the melting point.…”
Section: Evidence Of Hydrological Networkmentioning
confidence: 99%
“…Moreover, it is interesting to see if there is a relation between lakes and these subglacial features and if hydrological systems can be detected. Indeed, Siegert and Ridley (1998b) and Testut and others (2000) already suspected the existence of such a system above the Adventure Subglacial Trench.…”
Section: Introductionmentioning
confidence: 99%
“…The ice sheet surface represents a dynamic equilibrium surface resulting from the physical, dynamic, kinematic, and climatological processes acting on it, including its fl ow over the bedrock (Paterson, 1994). It therefore con-tains the signature of the main exogenous and endogenous processes, active or recent, from the regional to the local scale (Testut et al, 2000;Rémy et al, 2001;Frezzotti et al, 2002). Estimated ice velocities in the EAIS range from ~1 m/yr in the domal and/or ice divide regions to several tens of meters per year at its margin (Rignot et al, 2011).…”
Section: Introductionmentioning
confidence: 96%